Caracterização fenotípica de leveduras isoladas da mucosa vaginal em mulheres adultas - Corrêa, Paula dos Reis [UNESP]; David, Paulo Rodrigo dos Santos; Peres, Nathália Perpétua; da Cunha, Keith Cássia; de Almeida, Margarete Teresa Gottardo (My University, 2009)
PURPOSE: to characterize, phenotypically, yeasts isolated from the vaginal content of 223 symptomatic (S) and asymptomatic (A) adult women with vulvovaginitis, and to determine the clinical indicators which may lead to the appearance of signs and symptoms related to the mucosa involvement by this pathology. METHODS: a questionnaire with open and closed questions on epidemiological clinical data was applied initially. Then, mycological diagnosis with sowing in Chrom Agar Candida was done, followed by micro-morphological and biochemical identification. Specific methods for the detection of the virulence factors, proteinase and phospholipase were employed. Statistical analysis was performed through χ2 and Pearson's χ2 tests. RESULTS: the most prevalent species found was Candida albicans (87%, S and 67%, A) followed by Candida glabrata (4%, S e 17% A). The number of women reporting the use of contraceptives was higher among the symptomatic, 77%. In the two groups studied, about 87% of the women presented regular menstrual cycles and 57% were married with ages between 30 to 40 years old. Concerning the sexual practices, there has been concomitance among anal, oral and vaginal habits from the patients. Only Candida albicans produced the virulence factor phospholipase in 37.5% of them. Proteinase has been detected in Candida albicans, Candida glabrata and Candida parapsilosis. This latter virulence factor was mainly associated to isolates from symptomatic patients. CONCLUSIONS: it is a fact that the vaginal mucosa can be colonized and infected by yeasts, with several Candida species present. Nevertheless, Candida albicans is the most prevalent in the vaginal mucosa of adult women. It is evident the emergence of non-albicans Candida species, some of them with intrinsic resistance to azolics, such as Candida glabrata, Candida parapsilosis, Candida tropicalis, and Candida guillermondii, which can be explained by the inadequate use of medicines and empirical treatment.
Phenotypic characterization of yeasts isolated from the vaginal mucosa of adult women
Keywords: Candidiasis, vulvovaginal/epidemiologia; Risk factors; Signs and symptoms; Virulence factors; Vulvovaginitis